Offset or harmonious coexistence: untangling the interrelationship between green finance and rural revitalisation - Gao, Yi; Hua, Xiang; Sokolov, Boris Ivanovich; Zhao, Fangfei; Shen, Simin (Frontiers in Environmental Science, 2025)
Examining the relationship and its dynamics between green finance and rural revitalisation is crucial for achieving an equitable, sustainable economy and low-carbon transition. This paper develops a comprehensive evaluation system for green finance and rural revitalisation, utilising data from 31 provinces in China from 2000 to 2020, and reveals the coordinated relationship and spatial characteristics. From the system theory, the coordinated and interacting relationship between green finance and rural revitalisation and its geographic features are also described in this paper. The results show that green finance levels have significantly increased across 31 provinces in China. The rural revitalisation process is also moving forward, and there is mutual reinforcement that creates a balance of harmonious symbiosis and positive interaction between green finance and rural revitalization. The relationship between the two also exhibits distinct stages and notable regional disparities, resulting in a spatial and temporal pattern characterised by ‘high east, sluggish middle, and delayed in the west.’ At the same time, a pattern of green finance development has appeared in the demonstrative unit of development. However, to enable the revitalisation of rural areas through green policies, it must accelerate the development of rural revitalisation and provide more robust and focused policy support.